EXAMINING LOGICO-SEMANTIC RELATION IN INDONESIAN EFL STUDENTS’ WRITING IN SCHOOLING GENRES: SFL PERSPECTIVE - Lestari, Rina (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
Writing as a meaning-making is considered as a challenging task both for students and teachers, specifically related to the logical connection between clauses. Adopting Systemic Functional Linguistics (SFL) initiated by Halliday (1994) as framework, this qualitative study examined logical relations constructed in EFL students’ writings across four schooling genres; descriptive, argumentative, recount, and narrative texts to provide writing models for the EFL students and teachers in Indonesian context. The data comprised four high-achieving texts written by four ten graders of senior high school in West Java, Indonesia which were collected purposively based on their genre assessment conducted by the teacher. The collected data were sorted and categorized based on type and relation of the clauses. This textual analysis revealed that the four students employ complex clauses with different types of connections to express their ideas in a coherent and logical manner. The study also identified some weaknesses in the students’ writing that an SFL genre-based pedagogy could address. The study contributes to the understanding of the logico-semantic features of various academic genres in the Indonesian context and offers implications for EFL writing practitioners and scholars.